PENGARUH KEGIATAN PRACTICAL LIFE TERHADAP KEMANDIRIAN ANAK USIA 2-3 TAHUN DI BABYBOSS HOUSE KOTA PADANG - Mayshelly, Elza; Serli Marlina; Indra Yeni; Vivi Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The different degrees of independence seen in the two to three-year-old toddlers at Babyboss House in Padang City served as the impetus for this study. "Practical life" daily living activities are one type of activity that can be used to help youngsters develop their coordination, focus, discipline, responsibility, and independence. The purpose of this study was to ascertain how practical life activities affected the independence of two to three-year-old children at Babyboss House in Padang City. A quasi-experimental method with a non-equivalent control group design was used in the quantitative approach. A preschool class (experimental group) and a regular class (control group), each with 13 children, made up the sample. The study population totalled 39 children. Tests, observations, and documentation were used in the data collection process, with an independence assessment sheet serving as the instrument. Normality checks, homogeneity tests, independent sample t-tests, and effect size computations using SPSS software were all part of the data analysis process. According to the findings, children in the experimental group saw a greater improvement in their independence abilities than children in the control group. The experimental group's mean post-test score was 25.08, while the control group's score was 18.46.After hypothesis testing produced a Sig. (2-tailed) value of 0.000 (< 0.05), Ha was accepted and H₀ was rejected. Practical life activities have a significant impact on improving the independence of children aged 2-3 years at Babyboss House, Padang City, according to the computed effect size of 3.8, which falls into the "very large effect" category.